TINJAUAN SOSIAL EKONOMI DESA TUMBANG PAYANG DI SEKITAR HUTAN PT. SARPATIM, KALIMANTAN TENGAH - Herianto, Herianto (J-SEA (JOURNAL SOCIO ECONOMIC AGRICULTURAL), 2018)
Tumbang Payang Village community in fulfilling the needs of his life is still very dependent on the natural resources of the surrounding forest. Most subsistence and community income come from forest products such as timber and non timber. The livelihood of the community is almost 75% as a farmer and the remaining 25% as employees, traders, crafts and laborers. Other livelihoods of different communities, the results of participatory identification are known about 25 types of economic activities of the community. Variety of economic activities in general is a combination of activities in agriculture with activities outside agriculture such as trade, labor, livestock, fishing, timber and nontimber forest products, gaharu, rubber collectors, rice milling services, and others. The form of widespread land use is the garden covering about 10.76% of the total area. The plantation land is mostly rubber plantation and the rest are rattan garden, coconut, fruit, and mixed crops.